A Multisurface Interpersonal Circumplex Assessment of Rejection Sensitivity. Issue 1 (2nd January 2017) - Cain, Nicole M.; De Panfilis, Chiara; Meehan, Kevin B.; Clarkin, John F.
ABSTRACT: Individuals high in rejection sensitivity (RS) are at risk for experiencing high levels of interpersonal distress, yet little is known about the interpersonal profiles associated with RS. This investigation examined the interpersonal problems, sensitivities, and values associated with RS in 2 samples: 763 multicultural undergraduate students (Study 1) and 365 community adults (Study 2). In Study 1, high anxious RS was associated with socially avoidant interpersonal problems, whereas low anxious RS was associated with vindictive interpersonal problems. In Study 2, we assessed both anxious and angry expectations of rejection. Circumplex profile analyses showed that the high anxious RS group reported socially avoidant interpersonal problems, sensitivities to remoteness in others, and valuing connections with others, whereas the high angry RS group reported vindictive interpersonal problems, sensitivities to submissiveness in others, and valuing detached interpersonal behavior. Low anxious RS was related to domineering interpersonal problems, sensitivity to attention-seeking behavior, and valuing detached interpersonal behavior, whereas low angry RS was related to submissive interpersonal problems, sensitivity to attention-seeking behavior, and valuing receiving approval from others. Overall, results suggest that there are distinct interpersonal profiles associated with varying levels and types of RS.